2019
DOI: 10.1111/pace.13610
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect life‐threatening arrhythmias in ICDs using single‐chamber detection criteria

Abstract: Background There are anecdotal reports of sudden death despite a functional implantable cardioverter defibrillator (ICD). We sought to describe scenarios leading to fatal or near‐fatal outcome due to inappropriately inhibited ICD therapy in devices programmed with single‐chamber detection criteria. Methods Programmed settings, episode lists, and intracardiac electrograms from 24 patients with a life‐threatening event (n = 12) or fatal outcome (n = 12) related to failed ventricular arrhythmia detection were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…However, multiple reports have revealed that generic compliance with guideline-directed ICD programming recommendations, with or without undersensing, may lead to delayed, or in some instances even withholding, delivery of the HV therapy. 13 , 14 , 15 , 23 Moreover, postmortem studies suggest that mortality in ICD-implanted patients can be due to undertreated ventricular tachyarrhythmias. 13 , 18 , 24 , 25 It is well recognized that undersensing of ventricular signals (R waves) during VF in ICDs is a known limitation of the therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, multiple reports have revealed that generic compliance with guideline-directed ICD programming recommendations, with or without undersensing, may lead to delayed, or in some instances even withholding, delivery of the HV therapy. 13 , 14 , 15 , 23 Moreover, postmortem studies suggest that mortality in ICD-implanted patients can be due to undertreated ventricular tachyarrhythmias. 13 , 18 , 24 , 25 It is well recognized that undersensing of ventricular signals (R waves) during VF in ICDs is a known limitation of the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of these episodes suggests that inadequate discriminator programming resulted in incorrect rhythm diagnosis. Stroobandt and colleagues 14 demonstrated that SVT discriminators are crucial in reducing inappropriate therapy, with far-field morphology discriminator particularly effective. Programming of available discriminators, regardless of device manufacturer, is recommended by expert guidelines and is key to reducing inappropriate HV therapy delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphic VT and ventricular fibrillation (VF) with unstable, sensed R-R intervals as well as VT of a single morphology and unstable R-R intervals have also been implicated in withholding of appropriate ICD therapy. 5 SVT discriminators function in an ICD to differentiate supraventricular tachyarrhythmias from VT / ventricular fibrillation in order to avoid inappropriate therapy. In Medtronic devices, these complement the basic tachycardia detection algorithm within the VT zone: consecutive R-R intervals shorter than the programmed VT detection cycle length are counted until that number reaches the programmed number of intervals to detect (NID), at which point VT is detected.…”
Section: Key Teaching Pointsmentioning
confidence: 99%
“… 4 , 5 These changes in recommended programming can lead to delayed or undelivered therapy for polymorphic ventricular tachycardia and ventricular fibrillation (VF). 6 , 7 …”
Section: Introductionmentioning
confidence: 99%